PENDIDIKAN KEIMANAN DAN PEMBENTUKAN KEPRIBADIAN MUSLIM - Hamzah Lubis, Amir (Darul Ilmi: Jurnal Ilmu Kependidikan dan Keislaman, 2016)
One aspect of personal development is the education of children in the Islamic faith. Parents and teachers are responsible to optimize the implementation of faith education for children as fundamental to shape Muslim personality. Family education in Islam is relying on the cultivation of religious beliefs, and attitudes to foster moral virtue.